Pelatihan navigasi berbasis Global Position System (GPS) dan aplikasi pemetaan kehutanan bagi masyarakat pengelolaan hutan adat Ghimbo Pomuan, Kampar, Riau - Hanifah Ikhsani; Muhammad Ikhwan; Ika Lestari (TEKMULOGI: Jurnal Pengabdian Masyarakat, 2023)
Sustainable forest utilization is one of the objectives of forest management activities. The participation of the community and parties in managing forests is optimal, especially in the Ghimbo Pomuan customary forest, which is very much needed in collecting data on customary forest resources. The survey activity is the collection of information about forest resources that requires the ability to navigate using GPS for customary forest communities as forest managers. Also, being able to operate mapping applications such as ArcGIS is very necessary in order to be able to know the potential of the area in a comprehensive manner. The activity method given to partners is delivering material, discussion, demonstration, and evaluation. Submission of materials on navigation in the forestry sector, use of GPS and mapping. After the material was delivered, it was followed by demonstrations on the use of GPS and mapping training. In this community service activity, mentoring and evaluation activities are also carried out to measure the level of knowledge and skills of partners before and after community service activities are carried out. Based on the results of community service activities that have been carried out, there has been an increase in the knowledge and understanding of the surrounding community about how to use GPS and ArcGIS for managers of the Ghimbo Pomuan Customary Forest area, from 43.33% ignorant and 36.11% ignorant to 93.34% knowledgeable and 6.66% know.